CRYPTOCURRENCY AS NEW ECONOMIC AND LEGAL PHENOMENON - V. Shaydullina (Publishing House of the State University of Management, 2018)
This article presents the main economic and legal approaches to determining the status of the cryptocurrency. It is proved that the establishment of effective regulation of the crypto currency is impossible without an understanding of its economic nature. Cryptocurrency is regarded as a currency (digital or virtual currency, analogue of the currency, money), as a universal financial instrument, commodity (property, asset, property), money surrogate. There are the main conceptual recommendations for the regulation of the cryptocurrency as a new economic and legal phenomenon.